William James' The Varieties of Religious Experience Revisited - Hart, Curtis W. (Journal of religion and health, 2008)
This essay addresses the familial, religious, and cultural context for the writing and presentation of William James' classic work The Varieties of Religious Experience. The essay emphasizes the importance of the impact of Henry James, Senior, upon his son. This relationship along with a severe cardiac condition contributed to James' taking on and carrying through with his exploration of religious experience. The article explores The Varieties and concludes with a discussion of the importance of James' use of narrative to the study of mind-body medicine. This paper was originally presented at the Richardson Research Seminar in the History of Psychiatry at Weill Cornell Medical College.